2018
DOI: 10.1007/s00402-018-2944-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of osteochondral defects with a combination of bone grafting and AMIC technique

Abstract: Significant improvement of knee function and restoration of homogenous cartilage morphology could be achieved with simultaneous AMIC procedure and bone grafting in 2/3 of all patients with large osteochondral lesions at 4 years postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
2
18
0
2
Order By: Relevance
“…None of the case reports excluded described an adverse event, but rather correspond to early clinical experience including technical tools. Finally, 12 reported clinical series were included, reporting outcomes from 375 patients corresponding to the following references as summarized in Table 1: A, 20 B, 21 C, 22 D, 23 E, 24 F, 25 G, 26 H, 27 I, 28 J, 29 K, 30 and L. 31 32,33 Once the membrane was placed over the microfractured defect by gluing, the stable position of the membrane was checked by flexing and extending the joint 10 times. • • In one study center, MFx was not always used but rather replaced or complemented by stem cell transplantation (study F, Gobbi et al 25 ), or not used at all and only bone marrow concentrate was used (study E, Skowronski et al 24 ).…”
Section: Results From the Data Search And Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…None of the case reports excluded described an adverse event, but rather correspond to early clinical experience including technical tools. Finally, 12 reported clinical series were included, reporting outcomes from 375 patients corresponding to the following references as summarized in Table 1: A, 20 B, 21 C, 22 D, 23 E, 24 F, 25 G, 26 H, 27 I, 28 J, 29 K, 30 and L. 31 32,33 Once the membrane was placed over the microfractured defect by gluing, the stable position of the membrane was checked by flexing and extending the joint 10 times. • • In one study center, MFx was not always used but rather replaced or complemented by stem cell transplantation (study F, Gobbi et al 25 ), or not used at all and only bone marrow concentrate was used (study E, Skowronski et al 24 ).…”
Section: Results From the Data Search And Meta-analysismentioning
confidence: 99%
“…Study K 30 No intraoperative or postoperative complications reported. Study l 31 No intraoperative or postoperative complications reported.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 94%
“…Seven studies of the systematic review were excluded from the meta-analysis for the following reasons: preliminary data of the same survey (3 studies), 23,29,30 no clinical scores (1 study), 33 no standard deviation reported (3 studies). 26,32,35 Thus, 16 studies (for a total of 20 study groups) [13][14][15][16][17][18][19][20][21][22]24,25,27,28,31,34 were included in the quantitative synthesis.…”
Section: Clinical Scores Meta-analysismentioning
confidence: 99%
“…Pain evaluated with VAS was available for 289 patients in 12 studies (15 study groups). [13][14][15][16][17][18]20,22,24,27,28,31 In detail, 1-year VAS follow-up was available for 237 patients (11 study groups in 10 studies), 2-year follow-up for 253 patients (12 study groups in 9 studies), and ≥3-year followup (mean 48.8 ± 9.0 months from surgery) for 58 patients (4 study groups in 4 studies). Compared with the basal score, the meta-analysis on VAS showed a mean improvement of 37.6 (95% CI 31.8-43.4, I 2 = −29%) at 1-year follow-up, 39.1 (95% CI 34.0-44.3, I 2 = −64%) at 2-year follow-up, and 40.0 (95% CI 24.7-55.4, I 2 = −20%) at ≥3year follow-up (Fig.…”
Section: Clinical Scores Meta-analysismentioning
confidence: 99%
“…1,13,14,31 Previous studies that have investigated short-and medium-term follow-up cohorts suggest that AMIC in cartilage repair is a safe and effective treatment option that improves patient outcome measures and pain. 4,13,14,17,21,31,38 To assess extended effectiveness and reliability of the AMIC procedure as well as the durability of the repaired cartilage, long-term follow-up is essential. One study provided longer term data after an AMIC procedure, in which significant clinical and functional improvement was maintained over a 7-year follow-up, but this was a small cohort of 21 patients.…”
mentioning
confidence: 99%